PENGARUH PENDIDIKAN DASAR ANGGOTA TERHADAP KEWAJIBAN DAN TANGGUNGJAWAB ANGGOTA PADA CU MUARE PESISIR SIANTAN - Syafrianti, Husna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research is to know the influence of members basic training towards members responsibility and obligation in CU Muare Pesisir Kantor Pelayanan Siantan. The method in this research is the descriptive analyse method. This is an ex post facto reasearch. The population in this research is 318 members. The number of samples in this reasearch is 77 members. Data collection techniques in this reasearch are direct communication techniques (interview guidelines), indirect communication techniques (questionnaire), and documentary techniques (data of members stuck credits). The results of this research showed that there is the positive influence of members basic training towards members responsibility and obligation in CU Muare Pesisir Kantor Pelayanan Siantan. This can be known from the t value is 5.632 which shows there is influence of members basic training towards members responsibility and obligation outcome. When it compared with the t table on the significance level of 0.05 of 1.992, so that Ha is accepted. The conclusion of this research is members basic training has a significant effect on the members responsibility and obligation in CU Muare Pesisir Kantor Pelayanan Siantan Keywords: CU, Members Basic Training, Members Responsibility and Obligation